Parameters for Evolutive Social Housing Projects in Brazil: Contributions from Experiences in Portugal - Luciana Guimarães Teixeira Santos; Ana Kláudia Perdigão; Filipa Roseta (Buildings)
In Brazil, social housing is standardized into two-bedroom units, even when the beneficiary families have been previously identified. In Portugal, despite standardization, housing projects have adopted the concept of evolutionary housing. These are flexible proposals with typological diversity, allowing for a variety of family arrangements. While numerous studies analyze the quality of Brazilian housing projects, few of these studies have directly influenced the reality of the projects implemented. Thus, this study seeks to identify clear and objective parameters that can be applied to the design of social housing projects in Brazil. The evaluation of evolutionary social housing projects used in the resettlement process of Lisbon social neighborhoods was based on the housing program developed by the Laboratório Nacional de Engenharia Civil of Portugal. The findings consist of reference percentages indicating the necessary increases in minimum areas, according to the adopted housing typology, to enable project evolution. By systematizing design practices, this study aims to contribute to the dissemination and application of flexibility as a requirement in the conception of social housing proposals in Brazil, improving the ability to meet residents’ needs and enhancing the quality of life for the most vulnerable populations.